Peran person job fit dan job crafting terhadap niat mengundurkan diri dari pekerjaan pada pegawai kontrak - Ariyani, Yeni; Djudiyah, Djudiyah; Syakarofath, Nandy Agustin (Universitas Brawijaya, 2023)
The present study examined the effect of person-job fit and job crafting on contract employees’ turnover intention. The participants were 135 contract employees of state-owned (BUMN) and private enterprises (BUMS) in Palangkaraya Raya city. They recruited using the quota sampling technique. Three scales were deployed, namely the person-job fit scale, job crafting scales, and turnover intention scales. The collected data were analyzed using multiple linear regression. The result indicating that person-job fit and job crafting affect the employee’s turnover intention. In other words, contract employees with adequate job fit levels and good crafting exhibited low turnover intention. The turnover intention was affected by person-job fit and job crafting. When an employee has the qualifications corresponding to his job position and gets the opportunity to develop his potential the chances of turnover intention are small.